2015
DOI: 10.1002/2014wr016717
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic human health risk assessment of degradation‐related chemical mixtures in heterogeneous aquifers: Risk statistics, hot spots, and preferential channels

Abstract: The increasing presence of toxic chemicals released in the subsurface has led to a rapid growth of social concerns and the need to develop and employ models that can predict the impact of groundwater contamination on human health risk under uncertainty. Monitored natural attenuation is a common remediation action in many contamination cases. However, natural attenuation can lead to the production of daughter species of distinct toxicity that may pose challenges in pollution management strategies. The actual th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 63 publications
(71 reference statements)
3
37
0
Order By: Relevance
“…We observed that increasing σY2, τ 50 decreases in case of FP injection and increases in case of RC injection. Given that the risk is influenced by the ratio between the travel time and the characteristic time of reaction [ Henri et al ., ], different injection modes may lead to different impacts on the degradation of reactive substances, thereby producing different toxic daughter compounds at the extracting well, in case for instance of chlorinated solvents. Furthermore, τ 90 grows dramatically with σY2 in case of RC injection, reaching a difference of 1 order of magnitude with the FP case when σY2=8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that increasing σY2, τ 50 decreases in case of FP injection and increases in case of RC injection. Given that the risk is influenced by the ratio between the travel time and the characteristic time of reaction [ Henri et al ., ], different injection modes may lead to different impacts on the degradation of reactive substances, thereby producing different toxic daughter compounds at the extracting well, in case for instance of chlorinated solvents. Furthermore, τ 90 grows dramatically with σY2 in case of RC injection, reaching a difference of 1 order of magnitude with the FP case when σY2=8.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Henri et al . [], the solute injection mode has a significant impact on the probability of the extreme events (i.e., probability of exceeding a high concentration threshold).…”
Section: Mathematical Frameworkmentioning
confidence: 99%
“…Direct upscaling is typically challenged in real field applications by the presence of hydraulically connected features [ Trinchero et al ., ; Pedretti et al ., ], often exceeding the size of the model representative volume. The spatial distribution of highly permeable persistent geological bodies that concentrate solutes in connected channels controls not only the arrival of toxic concentrations and its subsequent risk to human life or ecosystems [ Henri et al ., ; Fiori et al ., ] but also the occurrence of biochemical reactions [ Rubol et al ., ; Sanchez‐Vila et al ., ], as they provide most of the nutrients that are vital to ecological systems. The representation of connected features in stochastic theories is still a major challenge.…”
Section: Reactive Transport: Process Description Observables and Momentioning
confidence: 98%
“…As an additional and challenging test case, we then consider the performance of our reduced order modeling strategy to model chemical transport in a heterogeneous porous medium. In this context, modern probabilistic approaches to environmental risk quantification [4,6,22,46] rely on the assessment of the probability that concentration of a given chemical species at a target environmental location exceeds a given threshold value, which is typically linked to human health or to environmental constraints. Other environmental performance metrics of interest in the context of the environmental risk assessment associated with solute migration in the subsurface include, e.g., peak values of concentrations, and/or early/late times of arrival of solute at sensitive locations in the aquifer [3].…”
Section: Application Of Pod To Advective-dispersive Transport Driven mentioning
confidence: 99%